Pengaruh Tingkat Kecerahan Layar Smartphone terhadap Daya Tahan Baterai - Adelyna Oktavia Nasution; Amanda Putri Rizkita; Raisya Aulia; Al Hafiz Okliano Hardianta; Rizkan El Fattah (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study examines user awareness of the influence of smartphone screen brightness on battery power consumption. Of the 80 respondents, 100% answered "No" to the question of using the battery monitoring app, indicating the low utilization of power efficiency features. Conversely, on the question of whether high brightness drains the battery quickly, 0% who answered "No", signifying full awareness of the negative impact of high brightness. Practical tests support this finding: battery consumption rises from 3% (20% brightness) to 7% (100% brightness) in 30 minutes. The results show high awareness, but adequate efficient action has not been followed.